Characterization of minerals, metals, and materials : proceedings of symposium - Hwang, Jiann-Yang (John Wiley & Sons, 2012)
This state-of-the-art reference contains chapters on all aspects of the characterization of minerals, metals, and materials. The title presents papers from one of the largest yearly gatherings of materials scientists in the world and thoroughly discusses the characterization of minerals, metals, and materials The scope includes current industrial applications and research and developments in the following areas: Characterization of Ferrous Metals Characterization of Non-Ferrous Materials Characterization of Minerals and Ceramics Character.
Keywords: Materials -- Testing -- Congresses.; Materials -- Analysis -- Congresses.; elektronické knihy; electronic books